Österreichische Literatur in der Zeitschrift "Wiadomości Literackie" in der Zwischenkriegszeit - Hurnikowa, Elżbieta (International Studies. Interdisciplinary Political and Cultural Journal, 2016)
The article is devoted to reception of Austrian literature before the Second World War in Wiadomości Literackie (Literary News). It was the most popular letter, whose aim was to educate society, and popularize foreign literature and culture. The literature that was most often promoted was French literature, but also German-speaking authors (cited in the article) were discussed. Austrian literature was not treated as distinct from German literature during that time but nontheless, the articles presents artists, of Austrian origin: Joseph Roth, Stefan Zweig, Rainer Maria Rilke, Hugo von Hofmannsthal, Arthur Schnitzler, Odon von Horváth, Franz Werfel and others. The article examines interviews with these writers as well as reviews their books and other texts which appeared in Wiadomości Literackie.